METHODOLOGICAL RECOMMENDATIONS FOR THE ORGANIZATION AND CONDUCTING PRACTICAL PREPARATION OF THE FUTURE PRESCHOOL EDUCATION SPECIALIST (Pedagogy of Higher and Secondary Education, 2008)
In the article under consideration the effective conditions of the practical training and developing of creative personality of future teachers who are present students of the pedagogical department are considered by the author.